3D cosmic-ray muon tomography using portable muography detector. (5th January 2022) - Chaiwongkhot, K.; Kin, T.; Nagata, Y.; Komori, T.; Okamoto, N.; Basiri, H.
Abstract: A feasibility demonstration of three-dimensional (3D) muon tomography was performed for infrastructure equivalent targets using the proposed portable muography detector. For the target, we used two sets of lead blocks placed at different heights. The detector consists of two muon position-sensitive detectors, made of plastic scintillating fibers (PSFs) and multi-pixel photon counters (MPPCs) with an angular resolution of 8 msr. In this work, the maximum likelihood-expectation maximization (ML-EM) method was used for the 3D imaging reconstruction of the muography. For both simulation and experiment, the reconstructed positions of the blocks produce consistent results with prior knowledge of the blocks' arrangement. This result demonstrates the potential of the 3D tomographic imaging of infrastructure by using seven detection positions for portable muography detectors to image infrastructure scale targets.